Acetaminophen attenuates doxorubicin‐induced cardiac fibrosis via osteopontin and GATA4 regulation: Reduction of oxidant levels1. Issue 10 (20th June 2013) - Schunke, Kathryn J.; Coyle, Luke; Merrill, Gary F.; Denhardt, David T.
Abstract It is well documented in animal and human studies that therapy with the anti‐cancer drug doxorubicin (DOX) induces fibrosis, cardiac dysfunction, and cell death. The most widely accepted mechanism of cardiac injury is through production of reactive oxygen species (ROS), which cause mitochondrial damage, sarcomere structural alterations, and altered gene expression in myocytes and fibroblasts. Here we investigated the effects of acetaminophen (APAP, N‐acetyl‐para‐aminophenol) on DOX‐induced cardiac injury and fibrosis in the presence or absence of osteopontin (OPN). H9c2 rat heart‐derived embryonic myoblasts were exposed to increasing concentrations of DOX ± APAP; cell viability, oxidative stress, and OPN transcript levels were analyzed. We found a dose‐dependent decrease in cell viability and a corresponding increase in intracellular oxidants at the tested concentrations of DOX. These effects were attenuated in the presence of APAP. RT‐PCR analysis revealed a small increase in OPN transcript levels in response to DOX, which was suppressed by APAP. When male 10–12‐week‐old mice (OPN+/+ or OPN−/−) were given weekly injections of DOX ± APAP for 4 weeks there was substantial cardiac fibrosis in OPN+/+ and, to a lesser extent, in OPN−/− mice. In both groups, APAP decreased fibrosis to near baseline levels. Activity of the pro‐survival GATA4 transcription factor was diminished by DOX in both mouse genotypes, but retained baseline activity in the presence of APAP. These effects were mediated, in part, by the ability of APAP, acting as an anti‐inflammatory agent, to decrease intracellular ROS levels, consequently diminishing the injury‐induced increase in OPN levels. J. Cell. Physiol. 228: 2006–2014, 2013. © 2013 Wiley Periodicals, Inc.